Ocena równowagi i położenia środka ciężkości u pacjentów po laryngektomii = The assessment of the balance and of the centre of gravity in patients after laryngectomy - Urszula Kaźmierczak; Aleksander Goch; Grzegorz Srokowski; Patrycja Kropkowska; Paweł Zniszczol; Agnieszka Radzimińska; Katarzyna Strojek; Walery Zukow (Kazimierz Wielki University, 2015)
Kaźmierczak Urszula, Goch Aleksander, Srokowski Grzegorz, Kropkowska Patrycja, Zniszczol Paweł, Radzimińska Agnieszka, Strojek Katarzyna, Zukow Walery. Ocena równowagi i położenia środka ciężkości u pacjentów po laryngektomii = The assessment of the balance and of the centre of gravity in patients after laryngectomy. Journal of Education, Health and Sport. 2015;5(10):275-283. ISSN 2391-8306. DOIhttp://dx.doi.org/10.5281/zenodo.33088 http://ojs.ukw.edu.pl/index.php/johs/article/view/2015%3B5%2810%29%3A275-283 https://pbn.nauka.gov.pl/works/665259 Formerly Journal of Health Sciences. ISSN 1429-9623 / 2300-665X. Archives 2011-2014http://journal.rsw.edu.pl/index.php/JHS/issue/archive   Deklaracja. Specyfika i zawartość merytoryczna czasopisma nie ulega zmianie. Zgodnie z informacją MNiSW z dnia 2 czerwca 2014 r., że w roku 2014 nie będzie przeprowadzana ocena czasopism naukowych; czasopismo o zmienionym tytule otrzymuje tyle samo punktów co na wykazie czasopism naukowych z dnia 31 grudnia 2014 r. The journal has had 5 points in Ministry of Science and Higher Education of Poland parametric evaluation. Part B item 1089. (31.12.2014). © The Author (s) 2015; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland and Radom University in Radom, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 05.08.2015. Revised 05.09.2015. Accepted: 20.10.2015.   Ocena równowagi i położenia środka ciężkości u pacjentów po laryngektomii The assessment of the balance and of the centre of gravity in patients after laryngectomy Kaźmierczak Urszula1, Goch Aleksander1, Srokowski Grzegorz1, Kropkowska Patrycja1, Zniszczol Paweł1, Radzimińska Agnieszka1, Strojek Katarzyna1, Zukow Walery2 1Katedra Fizjoterapii , Zakład Kinezyterapii i Masażu Leczniczego, Uniwersytet Mikołaja Kopernika w Toruniu Collegium Medicum w Bydgoszczy 2Instytut Kultury Fizycznej, Wydział Kultury Fizycznej, Zdrowia i Turystyki, Uniwersytet Kazimierza Wielkiego w Bydgoszczy   Słowa kluczowe: laryngektomia, równowaga, środek ciężkości. Keywords: laryngectomy, balance, center of gravity.   Streszczenie Krtań jest narządem odpowiedzialnym za tworzenie głosu, ochronę górnych dróg oddechowych, połykanie oraz poprzez kaszel oczyszczanie dolnych dróg oddechowych. Rak krtani, jest coraz częściej występującym nowotworem, którego formą leczenia jest radioterapia i zabieg chirurgiczny. Ważnym tematem jest wpływ nowotworu krtani i jego leczenia na równowagę i położenie środka ciężkości. Badanie przeprowadzono u 31 osób laryngektomowanych, spotykających się w klubie "Orion" w Bydgoszczy. Średnia wieku wynosiła 66,5. Grupę kontrolną stanowiły osoby zdrowe, bez zdiagnozowanych nowotworów głowy oraz zaburzeń równowagi. Badanie przeprowadzone było na platformie footscan i polegało na spokojnym staniu przez 10s z otwartymi, następnie z zamkniętymi oczami. Wyniki badania wskazują, że osoby po zabiegu laryngektomii mają zaburzenia równowagi. Całkowita długość ścieżki środka ciężkości jest większa niż u grupy kontrolnej. Dodatkowo pacjenci laryngektomowani cechują się większymi wychyleniami bocznymi i przednio-tylnymi niż osoby z grupy kontrolnej. Za kontrolę postawy odpowiedzialny jest układ przedsionkowy, propioceptywny oraz narząd wzroku. W obu grupach po wyłączeniu wzroku wyniki są słabsze niż przy oczach otwartych.   Abstract The larynx is the organ responsible for creating voice, the protection of the upper respiratory tract, swallowing and coughing treatment lower respiratory tract. Cancer of the larynx, is increasingly occurring malignant tumor, which form of treatment is radiation therapy, and surgery. An important theme is the effect of laryngeal cancer and its treatment on the balance and the position of the center of gravity. The study was conducted on 31 patients had laryngectomies, meeting in the Club "Orion" in Bydgoszcz. The average age amounted to 66.5. The control group were healthy people without diagnosed cancer of the head and balance disorders. The study was on the platform and the quiet of the footscan standing by 10s with open, then with eyes closed. The results of the test indicate that the person after laryngectomy have imbalances. The total length of the path of the center of gravity is greater than in the control group. In addition, had laryngectomies patients more deflections side and front-rear than those of the control group. Attitude control arrangement is atrial, proprioceptive and organ of sight. In both groups after turning off the visual results are weaker than when the eyes open.